2012
DOI: 10.1371/journal.pone.0042860
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Count and Neutrophil-Lymphocyte Count Ratio as Prognostic Markers in Patients with Bacteremia: A Retrospective Cohort Study

Abstract: IntroductionThere is scarce evidence on the use of eosinophil count as a marker of outcome in patients with infection. The aim of this study was to evaluate whether changes in eosinophil count, as well as the neutrophil-lymphocyte count ratio (NLCR), could be used as clinical markers of outcome in patients with bacteremia.MethodsWe performed a retrospective study of patients with a first episode of community-acquired or healthcare-related bacteremia during hospital admission between 2004 and 2009. A total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
124
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 32 publications
13
124
0
6
Order By: Relevance
“…Again, numerous studies suggested that NLR is an important criterion in making diagnostic and prognostic decisions in psoriasis, infective endocarditis, pneumonia, bacteremia and acute appendicitis. [13][14][15][16][17] In our study, we found that lymphocyte was higher in the patient group than the control group, and as a result, NLR was significant. This result supports the cause of chronic inflammation which plays an etiologic role in children with LAP.…”
Section: Discussionmentioning
confidence: 91%
“…Again, numerous studies suggested that NLR is an important criterion in making diagnostic and prognostic decisions in psoriasis, infective endocarditis, pneumonia, bacteremia and acute appendicitis. [13][14][15][16][17] In our study, we found that lymphocyte was higher in the patient group than the control group, and as a result, NLR was significant. This result supports the cause of chronic inflammation which plays an etiologic role in children with LAP.…”
Section: Discussionmentioning
confidence: 91%
“…Study from Netherlands reported that NLR >10 has 77.2% sensitivity and 63% specificity for predicting bacteremia 6 . Interestingly, another study reported that NLR with cut off >7 can be used as a prognostic marker in patients with bacteremia sepsis and in that study the NLR >7 was an independent risk factor for mortality in sepsis patients with bacteremia 18 . Acute physiology and chronic health evaluation (APACHE) II scoring system is designed to measure the severity of disease in patients admitted to the intensive care unit.…”
Section: Discussionmentioning
confidence: 96%
“…18 Some studies showed that NLR is promising marker in predicting bacteremia in patients with emergency medical admissions. [19][20][21] NLR was used as prognostic marker in patient with bacteremia. 20 We aimed to investigate whether NLR is a predictor of AKI in patients with septic shock.…”
Section: Introductionmentioning
confidence: 99%